Shorter versus longer corticosteroid duration and recurrent immune checkpoint inhibitor-associated AKI. Issue 9 (22nd September 2022) - Gupta, Shruti; Garcia-Carro, Clara; Prosek, Jason M; Glezerman, Ilya; Herrmann, Sandra M; Garcia, Pablo; Abudayyeh, Ala; Lumlertgul, Nuttha; Malik, A Bilal; Loew, Sebastian; Beckerman, Pazit; Renaghan, Amanda D; et al.
Abstract : Background: Corticosteroids are the mainstay of treatment for immune checkpoint inhibitor-associated acute kidney injury (ICPi-AKI), but the optimal duration of therapy has not been established. Prolonged use of corticosteroids can cause numerous adverse effects and may decrease progression-free survival among patients treated with ICPis. We sought to determine whether a shorter duration of corticosteroids was equally efficacious and safe as compared with a longer duration. Methods: We used data from an international multicenter cohort study of patients diagnosed with ICPi-AKI from 29 centers across nine countries. We examined whether a shorter duration of corticosteroids (28 days or less) was associated with a higher rate of recurrent ICPi-AKI or death within 30 days following completion of corticosteroid treatment as compared with a longer duration (29–84 days). Results: Of 165 patients treated with corticosteroids, 56 (34%) received a shorter duration of treatment and 109 (66%) received a longer duration. Patients in the shorter versus longer duration groups were similar with respect to baseline and ICPi-AKI characteristics. Five of 56 patients (8.9%) in the shorter duration group and 12 of 109 (11%) in the longer duration group developed recurrent ICPi-AKI or died (p=0.90). Nadir serum creatinine in the first 14, 28, and 90 days following completion of corticosteroid treatment was similar between groups (p=0.40, p=0.56, and p=0.89, respectively). Conclusion: A shorter duration of corticosteroids (28 days or less) may be safe for patients with ICPi-AKI. However, the findings may be susceptible to unmeasured confounding and further research from randomized clinical trials is needed.